Memorial Issue Dedicated to Dr. Howard D. Flack: The Man behind the Flack Parameter - Fromm, Katharina M.; Housecroft, Catherine (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The book is dedicated to the work and achievements of Howard Flack. It combines articles which describe his own work and the advances he made in the field of crystallography, with original research articles which focus on aspects related to Howard Flack's interests.